PERAN PENTING E-COMMERCE DALAM MENINGKATKAN PERKEMBANGAN UMKM DI KABUPATEN SITUBONDO - Pratiwi, Amesiella Agista; Nurfarida, Siti; Anwar, Jeny Dwi; Falintino, Gian; Ubaydillah, Mohammad; Rudyanto, Rudyanto; Faiza, Nur; Retnowati, Novita (Fakultas Ekonomi dan Bisnis, 2024)
Micro, Small and Medium Enterprises have an important role in regional and national economies. The aim of this research is to find out how big the influence of E-Commerce is on the development of MSMEs in Situbondo Regency. This type of research uses quantitative research. The type of data used in this research is primary data. The population in this research are MSMEs in Situbondo Regency who use E-Commerce for all their buying and selling activities. The sample used in this research was 100 MSME actors in Situbondo Regency. Data collection techniques use questionnaires and then process them using validity and reliability tests. The data analysis technique uses Smart PLS. The research results show that the P value is 0.000, where this value is smaller than the value of 0.050, so the data states that E-Commerce can significantly influence the development of Situbondo Regency MSMEs.